Diversity of Entamoeba spp. in African great apes and humans: an insight from Illumina MiSeq high-throughput sequencing. Issue 7 (June 2018) - Vlčková, Klára; Kreisinger, Jakub; Pafčo, Barbora; Čížková, Dagmar; Tagg, Nikki; Hehl, Adrian B.; Modrý, David
Graphical abstract: Highlights: Entamoeba haplotypes range from highly host specificity to low host specificity in the hosts studied. Most of the detected Entamoeba haplotypes belonged to the putatively commensal Entamoeba spp. Entamoeba histolytica was present in all host species but Entamoeba nuttalli only in humans and chimpanzees. Overlap of specific Entamoeba haplotypes observed among studied hosts suggests the zoonotic potential of certain haplotypes. Abstract: Understanding the complex Entamoeba communities in the mammalian intestine has been, to date, complicated by the lack of a suitable approach for molecular detection of multiple variants co-occurring in mixed infections. Here, we report on the application of a high throughput sequencing approach based on partial 18S rDNA using the Illumina MiSeq platform. We describe, to our knowledge, for the first time, the Entamoeba communities in humans, free-ranging western lowland gorillas and central chimpanzees living in the Dja Faunal Reserve in Cameroon. We detected 36 Entamoeba haplotypes belonging to six haplotype clusters, containing haplotypes possessing high and low host specificity. Most of the detected haplotypes belonged to commensal Entamoeba, however, the pathogenic species ( Entamoeba histolytica and Entamoeba nuttalli ) were also detected. We observed that some Entamoeba haplotypes are shared between humans and other hosts, indicating their zoonotic potential. The findings are important not only for understanding the epidemiology of amoebiasis in humans in rural African localities, but also in the context of wild great ape conservation.